2009
DOI: 10.1371/journal.pone.0005825
|View full text |Cite
|
Sign up to set email alerts
|

A Kinship-Based Modification of the Armitage Trend Test to Address Hidden Population Structure and Small Differential Genotyping Errors

Abstract: Background/AimsWe propose a modification of the well-known Armitage trend test to address the problems associated with hidden population structure and hidden relatedness in genome-wide case-control association studies.MethodsThe new test adopts beneficial traits from three existing testing strategies: the principal components, mixed model, and genomic control while avoiding some of their disadvantageous characteristics, such as the tendency of the principal components method to over-correct in certain situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…There are several other methods that take into account pedigree-based or empirically estimated kinship matrices in the statistical test 39-42 . One of the key differences between these methods and the mixed model methods, including EMMAX, is that the mixed model methods have a procedure for estimating the contribution of the kinship matrix to the phenotypes, whereas the other methods do not.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other methods that take into account pedigree-based or empirically estimated kinship matrices in the statistical test 39-42 . One of the key differences between these methods and the mixed model methods, including EMMAX, is that the mixed model methods have a procedure for estimating the contribution of the kinship matrix to the phenotypes, whereas the other methods do not.…”
Section: Discussionmentioning
confidence: 99%
“…However, as an alternative to mixed models, genotypes can be modeled using a fixed set of phenotypes, a theoretically appealing approach that makes fewer assumptions about phenotypic covariance structure3738. Simulations in the absence of unusually differentiated markers have shown that using the genotypic covariance matrix to account for both population and family structure can effectively control spurious associations under a variety of settings37 (ROADTRIPS; see Web Resources).…”
Section: Mixed Modelsmentioning
confidence: 99%
“…For unusually differentiated markers with allele frequency difference of 0.6 between the two populations, only EMMAX adjusting for PCs yielded a genomic control lambda parameter near 1.0. When the sample is composed of case-control data, recent methods such as ROADTRIPS [Rakovski and Stram, 2009;Thornton and McPeek, 2010], which model the genotypic covariance matrix to control for population and family structure has been shown to be advantageous.…”
Section: Discussionmentioning
confidence: 99%